2011
DOI: 10.1159/000333264
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Combination of Imaging Modalities in the Diagnosis of Hepatocellular Carcinoma Using Sonazoid®-Enhanced Ultrasound, Gadolinium Diethylene-Triamine-Pentaacetic Acid-Enhanced Magnetic Resonance Imaging, and Contrast-Enhanced Computed Tomography

Abstract: Objective: To clarify the diagnostic ability of combining imaging methods to diagnose hepatocellular carcinoma (HCC) using Sonazoid®-enhanced ultrasound (US), gadolinium diethylene-triamine-pentaacetic acid-enhanced (Gd-EOB-DTPA) magnetic resonance imaging (MRI), and contrast-enhanced computed tomography (CECT). Methods: A total of 32 patients who underwent surgical resection for HCC were studied. Sonazoid-enhanced US, Gd-EOB-DTPA MRI, CECT, and intraoperative contrast-enhanced ultrasonography were done for al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…It has actually become common to encounter cases where hypervascular HCC or nodule-in-nodule HCC that is undetectable by MDCT is detected in a routine screening by EOB-MRI because of early enhancement in the arterial phase or clear hypointensity in the hepatobiliary phase [11,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103]. Furthermore, studies comparing the diagnostic performance of EOB-MRI and MDCT for hypervascular HCC have shown that EOB-MRI is superior or, at the very l...…”
Section: Diagnostic Algorithmmentioning
confidence: 99%
“…It has actually become common to encounter cases where hypervascular HCC or nodule-in-nodule HCC that is undetectable by MDCT is detected in a routine screening by EOB-MRI because of early enhancement in the arterial phase or clear hypointensity in the hepatobiliary phase [11,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103]. Furthermore, studies comparing the diagnostic performance of EOB-MRI and MDCT for hypervascular HCC have shown that EOB-MRI is superior or, at the very l...…”
Section: Diagnostic Algorithmmentioning
confidence: 99%
“…CEUS is able to depict tumor vascularity sensitively and accurately [12,13,14,15,16]. In particular, when using only perfluorocarbon microbubbles (sonazoid), HCCs have been shown as defects during the Kupffer phase [10,17,18,19,20,21]. These defect lesions could be used as targets for the insertion of a RFA needle [22,23,24,25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, diagnosing the disease in the stage of hypovascular early hepatocellular carcinoma is considered to contribute to a better prognosis. For hyperarterialized moderately or more differentiated hepatocellular carcinoma, various imaging modalities show similar diagnostic performance, but it tends to be higher in Gd-EOB-MRI than in dynamic MDCT [65]. The degree of malignancy of nodules evaluated by CT with intra-arterial contrast injection and signal intensity in the hepatocyte phase of Gd-EOB-MRI are correlated with the degree of malignancy of borderline lesions, and the early liver cancer type was more markedly hypointense and detected more frequently than the DN type.…”
Section: Commentsmentioning
confidence: 99%